Sistem Pembersih Kaca dengan Mekanisme Gerak Motorik Pada Smart Aquarium Berbasis Internet of Things (IoT) - Dody Hidayat; Ramli Ramli (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Aquariums are decorative elements that not only serve to beautify a room, but also as artificial habitats for fish and other aquatic creatures. One of the main problems in maintaining an aquarium is keeping the glass clean from algae and dirt that can interfere with the aesthetics and comfort of the creatures inside. Previous research has focused on Internet of Things (IoT)-based water control and lighting systems, but has not yet covered the aspect of automatic glass cleaning. Manual cleaning requires time and effort, and if not done regularly, can lead to a decline in the quality of the aquarium environment. This study aims to design and develop a glass cleaning system with a motorized mechanism for an IoT-based smart aquarium. The system is designed to operate automatically or via remote control using a smartphone. The cleaning mechanism is activated based on the detection of dirt through a turbidity sensor that measures the level of clarity or turbidity of the water due to algae build up. The turbidity sensor is also used as the main trigger for glass cleaning. The hardware used includes a drive motor (stepper), turbidity sensor, and NodeMCU ESP32 microcontroller connected to the Blynk Cloud platform for control and monitoring via a mobile application. The results of this study are a prototype of an efficient, responsive, and easy-to-operate IoT-based aquarium glass cleaning system that can improve the convenience of aquarium maintenance automatically and in real-time.